ANALYSIS OF THE EDUCATIONAL VALUES OF THE MAIN CHARACTER IN THE MOVIE FRONT OF THE CLASS - Muhammad Fiqrial Adiyat; Lalu Muhaimi; Santi Farmasari (Journal of English Education Forum (JEEF), 2023)
The purposes of this study are to identify Brad Cohen characterization in front of the class movie by using Minderop theory about the method of analyzing the characterization (2005), and to describe the educational values from Brad Cohen is characterization. In addition, after analyzing the characterization of Brad Cohen there are five major characters found, there are self- confident, care, persistent, patient, and brave. Those five characters are related to the educational values covering justice, democratic value and respect. These findings are resulted from the analysis of the data under the application of qualitative descriptive design.